The Effect Of Coordination Exercises Using Assisting Aids On The Development of Motor Speed For Dribbling Skill In Youth Soccer - Naji, Deyaa (Journal of Physical Education, 2016)
The dribbling football skill is considered to be the main key by which can carry out the tactical duties during a match. Without mastering the required motor speed, the task of implementing these plans becomes very difficult due to the correlation between the basic skills and the physical abilities especially that of motor speed. Hence the idea of the research in conducting an experimental scientific study giving special coordinative exercises (of acumen and intelligence) using training aids with balls of different shapes and sizes and with alternate hands and legs to develop the motor speed of dribbling skill .The study has been applied to Al-Sulaikh Sports Club players of youth as the subjects of the study. They have been divided into two groups; experimental and control each of (10) players. The study started on Sunday, 14/2/2016 until Thursday, 7/4/2016 with three training units weekly; for 8 weeks and in totally (24) units. The training unit was mainly occupied by the coordinative exercises and for (30-40) minutes. The exercises were coordinately changed using balls of different shapes and sizes and with alternate arms and legs to develop motor speed of dribbling skill .Posttests then took place on Sunday, 10/4/2016; results and data were collected, statistically treated, displayed, and scientifically discussed.